Analisis Strategi Peningkatan Kepercayaan Investor Pasca Skandal Laporan Keuangan : Studi Kasus pada Stratup eFishery - Sakina Papalia; Ainun Arizah (AKUNTANSI 45, 2025)
The financial reporting scandal that struck eFishery in early 2024 triggered a major trust crisis among investors and other stakeholders. This article aims to analyze the strategies implemented by eFishery to restore investor confidence following the scandal and evaluate their broader impact on Indonesia’s startup ecosystem. The research adopts a descriptive qualitative approach with a case study method, relying on secondary data from news articles, audit reports, and academic literature on corporate governance and investor trust. The analysis reveals that eFishery employed strategic actions such as management restructuring, independent auditing, internal disciplinary enforcement, policy reform, and transparency enhancement. These measures reflect the company's commitment to good corporate governance as a means of rebuilding credibility and investor confidence. The study also provides valuable insights for other startups in Indonesia on the importance of accountability and business ethics for long-term sustainability.